Invasion speeds in microbial systems with toxin production and quorum sensing. (7th May 2017) - Bewick, Sharon; Staniczenko, Phillip P.A.; Li, Bingtuan; Karig, David K.; Fagan, William F.
Abstract: The theory of invasions and invasion speeds has traditionally been studied in macroscopic systems. Surprisingly, microbial invasions have received less attention. Although microbes share many of the features associated with competition between larger-bodied organisms, they also exhibit distinctive behaviors that require new mathematical treatments to fully understand invasions in microbial systems. Most notable is the possibility for long-distance interactions, including competition between populations mediated by diffusible toxins and cooperation among individuals of a single population using quorum sensing. In this paper, we model bacterial invasion using a system of coupled partial differential equations based on Fisher's equation. Our model considers a competitive system with diffusible toxins that, in some cases, are expressed in response to quorum sensing. First, we derive analytical approximations for invasion speeds in the limits of fast and slow toxin diffusion. We then test the validity of our analytical approximations and explore intermediate rates of toxin diffusion using numerical simulations. Interestingly, we find that toxins should diffuse quickly when used offensively, but that there are two optimal strategies when toxins are used as a defense mechanism. Specifically, toxins should diffuse quickly when their killing efficacy is high, but should diffuse slowly when their killing efficacy is low. Our approach permits an explicit investigation of the properties and characteristics of diffusible compounds used in non-local competition, and is relevant for microbial systems and select macroscopic taxa, such as plants and corals, that can interact through biochemicals. Abstract : Graphical abstract: Abstract : Highlights: Analytical approximations are derived for invasion speeds with diffusible toxins. Fast toxin diffusion is always beneficial for offensive compounds. Fast toxin diffusion is beneficial for defensive compounds with high efficacy. Slow toxin diffusion is beneficial for defensive compounds with low efficacy. Quorum sensing can lead to bi-stability in bacterial invasion rates.